Alzheimer's β-secretase, β-site amyloid precursor protein-cleaving enzyme, is responsible for cleavage secretion of a Golgi-resident sialyltransferase - Kitazume, Shinobu (The National Academy of Sciences, 2001)
The deposition of amyloid β-peptide (Aβ) in the brain is closely associated with the development of Alzheimer's disease. Aβ is generated from the amyloid precursor protein (APP) by sequential action of β-secretase (BACE1) and γ-secretase. Although BACE1 is distributed among various other tissues, its physiological substrates other than APP have yet to be identified. ST6Gal I is a sialyltransferase that produces a sialylα2,6galactose residue, and the enzyme is secreted out of the cell after proteolytic cleavage. We report here that BACE1 is involved in the proteolytic cleavage of ST6Gal I, on the basis of the following observations. ST6Gal I was colocalized with BACE1 in the Golgi apparatus by immunofluorescence microscopy, suggesting that BACE1 acts on ST6Gal I within the same intracellular compartment. When BACE1 was overexpressed with ST6Gal I in COS cells, the secretion of ST6Gal I markedly increased. When APP(SW) (Swedish familial Alzheimer's disease mutation), a preferable substrate for BACE1, was coexpressed with ST6Gal I in COS cells, the secretion of ST6Gal I significantly decreased, suggesting that that the β-cleavage of overexpressed APP(SW) competes with ST6Gal I processing. In addition, BACE1-Fc (Fc, the hinge and constant region of IgG) chimera cleaved protein A-ST6Gal I fusion protein in vitro. Thus, we conclude that BACE1 is responsible for the cleavage and secretion of ST6Gal I.